Comparative Analysis of Cellular Immune Responses in Treated Leishmania Patients and Hamsters against Recombinant Th1 Stimulatory Proteins of Leishmania donovani - Joshi, Sumit; Yadav, Narendra K.; Rawat, Keerti; Tripathi, Chandra Dev P.; Jaiswal, Anil K.; Khare, Prashant; Tandon, Rati; Baharia, Rajendra K.; Das, Sanchita; Gupta, Reema; Kushawaha, Pramod K.; Sundar, Shyam; et al. (Frontiers in Microbiology, 2016)
Our prior studies demonstrated that cellular response of T helper 1 (Th1) type was generated by a soluble antigenic fraction (ranging from 89.9–97.1 kDa) of Leishmania donovani promastigote, in treated Leishmania patients as well as hamsters and showed significant prophylactic potential against experimental visceral leishmaniasis (VL). Eighteen Th1 stimulatory proteins were identified through proteomic analysis of this subfraction, out of which fifteen were developed as recombinant proteins. In the present work, we have evaluated these fifteen recombinant proteins simultaneously for their comparative cellular responses in treated Leishmania patients and hamsters. Six proteins viz. elongation factor-2, enolase, aldolase, triose phosphate isomerase, protein disulfide isomerase and p45 emerged as most immunogenic as they produced a significant lymphoproliferative response, nitric oxide generation and Th1 cytokine response in PBMCs of treated patients and lymphocytes of treated hamsters. The results suggested that these proteins may be exploited for developing a successful poly-protein and/or poly-epitope vaccine against VL.